Problematic Internet Use, Problem Solving Skills and Emotional Regulation Among Junior High School Students (Universitas Negeri Semarang, 2018)
This research was designed to examine the relationship between Problem Solving Skills (PSS), Emotional Regulation (ER) and Problematic Internet Use (PIU) among junior high school students. As many as 137 students from SMPN 10 Surabaya in the even semester of academic year 2017/2018 were chosen as participants by using quota sampling method. Data was captured using Problem Solving Inventory (PSI), Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA) and Generalized Problematic Internet Use 2 (GPIUS2). Data that has been collected then analyzed using computer program SPSS version 24.00. The statistical results show that there are low but definite negative relationship between PSS and ER on PIU (Î² = -0.18 and Î² = -0.21, p < 0.05, respectively). PSS and ER overall explained the 10% variance of PIU. Based on the results, it can be concluded that the higher level of PIU, the lower level of PSS and ER that students have. Thus further, the current research finding will be discussed later.